ANALISIS INDEKS KEPUASAN MASYARAKAT (IKM) TERHADAP PELAYANAN PUBLIK DI PUSKESMAS TEGALREJO KOTA SALATIGA TAHUN 2012 - Putra, Yanuar Surya (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2012)
AbstractService is a needs fulfillment process through other’s direct activity, and main goal of service is creating satisfaction for consumers. Every Organization who sell service have to provide a service with high quality, by that they can achieve those main goal which is consumer’s satisfaction. The aims of this research is to analyze an measure the service quality that given by public service organization who belongs to government in Salatiga. The organization is Puskesmas Tegalrejo, Puskesmas is a small medical service organization.The research method using Consumer’s Satisfication Index or Indeks Kepuasan Masyarakat (IKM) which is have 14 indicators to measure the quality of Puskesmas Tegalrejo service towards patients. Sampels of this research amount 150 people who became those Puskesmas patients.The result found that Puskesmas Tegalrejo have a good performance in service quality with score 63,59 altough there was two indicators that still not good enough if it measured by patients opinion. Those indicators was “speed of service” and “on time schedule of Service”. The conclusion stated that Puskesmas have to keep and maintain the “good” quality service, and still have to improve the “speed of service” and on time in service. Keywords: Service Quality, Indeks Kepuasan Masyarakat